2015
DOI: 10.1371/journal.pone.0141332
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prolonged Radiotherapy Treatment Time on Survival Outcomes after Intensity-Modulated Radiation Therapy in Nasopharyngeal Carcinoma

Abstract: PurposeTo estimate the influence of prolonged radiation treatment time (RTT) on survival outcomes in nasopharyngeal carcinoma after continuous intensity-modulated radiation therapy.Methods and MaterialsRetrospectively review 321 patients with NPC treated between October 2009 and December 2010 and all of them underwent simultaneous accelerated intensity-modulated radiation therapy. The fractionated dose was 2–2.47 Gy/F (median 2.27 Gy), and the total dose for nasopharyngeal region was 64–74 Gy/ 28–33 fractions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
5
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 39 publications
3
34
5
1
Order By: Relevance
“…Although the benefit of neoadjuvant chemotherapy or adjuvant chemotherapy is still open to debate, neoadjuvant chemotherapy or adjuvant chemotherapy is commonly prescribed for most patients with III-IV stage disease at our hospital. But it is worth noting that concurrent chemotherapy had no significant impact on PFS, LRFS or DFFS in our study and the previous study [10]. This may be caused by the fact that the subgroup receiving concurrent chemotherapy contained a significantly higher proportion of patients with locally advanced NPC.…”
Section: Discussioncontrasting
confidence: 74%
“…Although the benefit of neoadjuvant chemotherapy or adjuvant chemotherapy is still open to debate, neoadjuvant chemotherapy or adjuvant chemotherapy is commonly prescribed for most patients with III-IV stage disease at our hospital. But it is worth noting that concurrent chemotherapy had no significant impact on PFS, LRFS or DFFS in our study and the previous study [10]. This may be caused by the fact that the subgroup receiving concurrent chemotherapy contained a significantly higher proportion of patients with locally advanced NPC.…”
Section: Discussioncontrasting
confidence: 74%
“…Currently, there is a lack of consensus concerning what is considered as prolonged RT or interrupted RT, and the methods to quantify this are heterogeneous. For example, some authors have examined total RT duration, whereas others have examined the number of continuous days that RT was interrupted . Furthermore, the existing published data largely consists of retrospective data that is small in sample size .…”
Section: Discussionmentioning
confidence: 99%
“…For example, some authors have examined total RT duration, whereas others have examined the number of continuous days that RT was interrupted . Furthermore, the existing published data largely consists of retrospective data that is small in sample size . To our knowledge, there is only one published data in a large prospective cohort investigating this question, which is by Yao et al In this study of 447 patients, Yao et al found that RT interruption was significantly associated with locoregional failure survival (LRFS) in the multivariable analysis (HR = 9.64, 95% CI, 4.10–22.65), but RT interruption was not significantly associated with OS in the multivariable model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genetic susceptibility, environmental factors, exposure to chemical carcinogens, and Epstein-Barr virus (EBV) infection are considered the major reasons for this cancer type (Hildesheim & Wang, 2012). Radiotherapy alone or concurrent chemoradiotherapy are the main treatments for NPC patients and the survival rate has improved significantly especially in patients with locally and regionally advanced NPC (Baujat et al, 2006;Lee, Ma, Ng & Chan, 2015;Li et al, 2015). However, radiotherapy for NPC is notoriously difficult due to the invasive characteristics of the tumor, early local and distant metastasis; concomitant chemoradiotherapy-related toxicities (Du, Ying, Kong, Zhai & Hu, 2015;Jiang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%